Intestinal necrosis due to nonocclusive mesenteric ischemia in a child with Mycoplasma pneumoniae pneumonia: a case report - Xuejing Li; Tingting Lin; Ken Chen; Danli Wang; Jiahui Yu; Lei Wu; Lanfang Tang (BMC Infectious Diseases)
Abstract Background Mycoplasma pneumoniae is a pathogen that causes community-acquired pneumonia in children, and it is often accompanied by various extrapulmonary complications. While intestinal necrosis is relatively rare among these extrapulmonary manifestations, they can be severe and life threatening. Case presentation We present an uncommon extrapulmonary complication of intestinal necrosis caused by nonocclusive mesenteric ischemia (NOMI) in a six-year-old child with M. pneumoniae pneumonia. Although the patient exhibited segmental embolism in their pulmonary artery and right atrial appendage, neither computed tomography angiography nor postoperative pathology revealed mesenteric vascular thrombosis. The patient’s mesenteric arteries were patent without occlusion or thrombosis, and the pathological findings indicated ischemic enteritis, which is consistent with NOMI. Conclusions Intestinal necrosis caused by NOMI is a rare but severe extrapulmonary complication of Mycoplasma pneumoniae infection. Compared to acute occlusive mesenteric ischemia, diagnosing NOMI is significantly more challenging due to the inherent difficulty in detecting vasospasm through imaging studies, often resulting in delayed intervention and higher mortality. Thus, integrating other diagnostic methods, clinical manifestations, and multidisciplinary diagnosis and treatment in medical practice are essential for ensuring accurate diagnoses and appropriate treatment.